A technique for separating viable islets of Langerhans from a fragment of human pancreatic tail - A. S. Ponomareva; L. A. Kirsanova; N. V. Baranova; G. N. Bubentsova; I. A. Miloserdov; E. A. Volkova; V. I. Sevastyanov (Вестник трансплантологии и искусственных органов)
Introduction. Modern techniques of tissue engineering in the treatment of some degenerative diseases suggest the prospective viability of the biomedical technologies based on the creation of the equivalent of the damaged tissue (organ), including the tissue-engineered construct (TEC) of the endocrine pancreas (EP). Obtaining viable islets of Langerhans (IL) from the pancreas is a decisive step towards the creation of a TEC EP. The classic method of IL separation is based on enzymatic digestion of pancreatic tissue and further islet purification in ficoll density gradient during centrifugation, which adversely affects the morphofunctional state of IL.The aim of the study was the development of a method for separating viable pancreatic islets from a fragment of human pancreatic tail with different cold ischemia times.Materials and methods. A procedure of IL separation is proposed to be conducted without the use of EP tissue collagenase perfusion in the Ricordi chamber at the stage of IL separation and without ficoll solution with a varying density gradient at the stage of IL purification. Identification of IL obtained was performed by dithizone staining. The IL viability was evaluated using the LIVE/DEAD ® Cell Viability Kit. Histological analysis of the initial material included routine staining methods as well as immunohistochemical staining of the main types of islet cells.Results. The morphological study of the EP fragments at different times of cold ischemia did not reveal significant differences in the histological presentation of the organ parenchyma; the islet structure appeared intact. Vital staining confirmed the separated IL viability in vitro for at least 1–3 days.Conclusion. The proposed method of pancreatic tissue treatment allowed to reduce the number of stages, thereby minimizing the adverse effects of centrifugation and ficoll on the integrity of IL. It is possible to obtain the necessary amount of viable IL from a small EP fragment with the cold ischemia time of up to 19 hours, which can be used to create a TEC of a pancreas.